KEMAMPUAN MENULIS SURAT LAMARAN PEKERJAAN SISWA KELAS XII SMA NEGERI 13 PADANG - Latif, Arif; Chan, Wirsal; Adrias, Adrias (Pendidikan Bahasa Indonesia, 2014)
Writing the application letter is one of the skills that should be mastered by the students. That is why it is included into School Based Curriculum (KTSP). This research deals with the studentsâ ability in writing the application letter at grade XII of SMA N 13 Padang. This research is then focused on: (1) the letterâs form, (2) the capital letters, and (3) punctuations, included: (a) full stop, (b) comma, and (c) semi colon. The type of this research is descriptive quantitative. The findings of this research show that (1) the application of the letterâs form is categorized into good (84,5%), (2) the use of capital letters is also categorized into good (58,5%), (3) the use full stop is determined as sufficient (73%), (4) the use of comma is categorized into good (77,5%), and (5) the use of semi-colon is determined as sufficient (67,5%). Based on the data analysis, it can be concluded that the studentsâ ability in writing application letter at grade XII of SMA N 13 Padang is categorized into sufficient (72,5%).